Bone Biomarkers Based on Magnetic Resonance Imaging - Jerban, Saeed; Jang, Hyungseok; Chang, Eric Y.; Bukata, Susan; Du, Jiang; Chung, Christine B. (Seminars in Musculoskeletal Radiology, 2024)
Magnetic resonance imaging (MRI) is increasingly used to evaluate the microstructural and compositional properties of bone. MRI-based biomarkers can characterize all major compartments of bone: organic, water, fat, and mineral components. However, with a short apparent spin-spin relaxation time (T2*), bone is invisible to conventional MRI sequences that use long echo times. To address this shortcoming, ultrashort echo time MRI sequences have been developed to provide direct imaging of bone and establish a set of MRI-based biomarkers sensitive to the structural and compositional changes of bone. This review article describes the MRI-based bone biomarkers representing total water, pore water, bound water, fat fraction, macromolecular fraction in the organic matrix, and surrogates for mineral density. MRI-based morphological bone imaging techniques are also briefly described.
Keywords: magnetic resonance imaging; cortical bone; trabecular bone; biomarkers; ultrashort echo time